Film at the border: Memories of cinemagoing in Laredo, Texas. (January 2017) - Lozano, José Carlos
This article addresses the memories of 28 filmgoers between the ages of 64 and 95 in Laredo, Texas – a city located on the border between the United States and Mexico. It explores respondents' memories of US and Mexican films, actors and local venues against the historical background of a fluid and complex border. In particular, it examines the negotiation of cultural identities among residents with strong connections to Mexican heritage but who are also influenced by the structural characteristics of the American political, economic and educational systems.